Analisis Kelayakan Tangki Timbun CPO Kapasitas 500 dan 1000 Ton Berdasarkan Ketebalan Roundshell, Suhu, dan Tekanan Hidrostatis - Raja, Pada Mulia; Mahyunis, Mahyunis; Istiadzah, Tiara Briliani; Zakwan, Zakwan; Winardi, Rafeal Remit; Rahimah, Rahimah; Lubis, Zulyaden (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
This study aims to determine the feasibility of using 500-ton and 1000-ton Crude Palm Oil (CPO) storage tanks in a palm oil mill. The evaluation is based on the roundshell thickness, operating temperature, and hydrostatic pressure acting on the tanks. A descriptive quantitative method was applied using primary and secondary data from PMKS Simpang Gambir. The results showed that for the 500-ton tank, the calculated roundshell thickness is 8.6 mm, the actual is 8.87 mm, and the design is 9 mm, with a hydrostatic pressure of 5.73 Pa. For the 1000-ton tank, the calculated thickness is 13.1 mm, the actual thickness is 13.8 mm, and the design thickness is 14 mm, with a hydrostatic pressure of 11.46 Pa. The corrosion rates are 0.00072 mm/month and 0.0011 mm/month, respectively. Based on the analysis, the 500-ton tank is feasible for continued use for approximately 31 years, and the 1000-ton tank for 53 years, assuming constant corrosion rates.